渐开线直齿内齿轮的轮齿变形挠度解析 - 康焱; 石照耀; 林家春; 姚文席 (Jixie chuandong)
The first thing is to calculate the deformation of the loaded gear,when researching dynamic characteristic of the gear transmission and controlling the transmission quality.In order to deduce a simplified approximate formula to calculate the tooth deformation with deflection of the internal spur gear,the four main gear parameters which influence the tooth stiffness of the internal spur gear are selected:position of load action、number of teeth、addendum modification and tool edge radius,the research model of the gear using the table of the orthogonal design is scientifically choiced;Then,the tooth deformation with deflection of each research model is theoretical researched and practically calculated;At last,a simplified approximate formula to calculate the tooth deformation with deflection of the internal spur gear is deduced by Multivariate regression analysis,which base the nonlinear dynamics study of internal gear pair.